2010
DOI: 10.1093/intqhc/mzq058
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of the primary health-care satisfaction scale in Turkish women

Abstract: The present study provides evidence of the primary health-care satisfaction scale's validity, reliability and acceptability. This scale should be further evaluated with a larger representative sample of women seeking primary care in Turkey and diverse populations of the world. The scale has potential applications for use in research. The scale may be used both in studies to evaluative alternative models of primary care delivery for women and in quality improvement programs in women's primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…All instruments found were developed in the English language and there were only six cross-cultural adaptation papers 26,30,32,33,34,35 . The adaptation process to other languages and cultures is not simple and the scrutiny made by different researches on distinct sociocultural contexts would help to develop a reliable instrument 61,62,63 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All instruments found were developed in the English language and there were only six cross-cultural adaptation papers 26,30,32,33,34,35 . The adaptation process to other languages and cultures is not simple and the scrutiny made by different researches on distinct sociocultural contexts would help to develop a reliable instrument 61,62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though patient satisfaction has been widely studied in healthcare, no gold standard instrument or even a validated instrument was found for many different contexts 20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56 . The option to develop new instruments by the healthcare organizations can reflect the specificity of each culture or health settings, but, at the same time, this phenomenon can show a gap in state-of-the-art approaches in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that chronically ill and healthy respondents experienced the same satisfaction with community care services. Several studies [29-31] discussed the questionnaire’s design, validity and reliability as it related to patient satisfaction which found that nursing and doctor categories were most notable, and several studies approached different aspects of patient satisfaction [32,33]. …”
Section: Introductionmentioning
confidence: 99%
“…There are, however, also several questionnaires in which different kinds of items are applied together. 2 , 5 7 , 19 21 These questionnaires cannot be clearly classified as either scales or indices. However, in all of these questionnaires, the majority of the items address causes.…”
Section: Patient Satisfaction Questionnairesmentioning
confidence: 99%